مشكلة تنازع الجنسيات دراسة مقارنة في القانون الدولي و القانون السوري - جامع, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2017)
إن الجنسية نظام قانوني لا يخص الدولة فحسب بل هي وسيلة لتحديد عنصر السكان فيها و هو بالنسبة للمجموعة البشرية أداة لتوزيع الأفراد دوليا بين الوحدات السياسية الدول, تعتبر الجنسية بالنسبة للأفراد حق شخصي لمن يتمتع بها فيتوقف عليها تعيين مقدار الحقوق التي يتمتع بها و يتوقف عليها تعيين القانون الواجب التطبيق, لذا فمن الضرورة أن ينسب الفرد لدولة من دول العالم و يرتبط بها برابطة الجنسية و من مصلحته و حقه ان يدافع عن هذه الصفة و يلزم الدولة الاعتراف له بها و احترامها, يرتبط بقانون الجنسية مشكلة تنازع الجنسيات بنوعيها ازدواج الجنسية عندما يتمتع الفرد بأكثر من جنسية, و انعدام الجنسية في حالة عدم تمتع الفرد بأي جنسية و سنقوم في بحثنا بدراسة مشكلة تنازع الجنسيات بنوعيها و آثارها على الفرد و الدولة و المجتمع الدولي. nationality legal system that does not concern only the state but rather a means to determine the population element where and is for human tool set for the distribution of individuals internationally between states and political units, is considered sexual For individuals a personal right for those who enjoy it depends upon designate the amount of the rights enjoyed by and dependent upon appointment Applicable law, so it is necessary that the individual is attributed to the state of the world and the associated Association of nationality and of his interests and his right to defend this status and required the state to recognize him out and respected, is linked to nationality law problem of conflict of nationalities, both dual citizenship when he enjoys the individual more than one nationality, and statelessness in the case do not enjoy any individual nationality and we will in our study, both the problem of the conflict of nationalities and their effects on the individual and the state and the community international